Are the monophlebid genera Drosichoides Morrison and Buchnericoccus Reyne synonyms? (Hemiptera, Coccomorpha, Monophlebidae) - Wu, Bo-Wen; Wu, San-An (Zootaxa, 2018)
The morphology of the adult male of Drosichoides ?haematoptera (Cockerell) is redescribed and illustrated and the adult female of Buchnericoccus sp. (Hemiptera: Monophlebidae) is also described and illustrated. These male and female specimens perhaps are conspecific. Genus Buchericoccus Reyne may be a junior synonym of genus Drosichoides Morrison.